Developing an idea of precast concrete installer (PCI) robot / Amalinda Othman and Siti Akhtar Mahayuddin - Othman, Amalinda; Mahayuddin, Siti Akhtar (2019)
The implementation of Industrialized Building System (IBS) has increasingly widespread as the government emphasized the importance of prefabricated process in IBS Roadmap. Somehow, the installation of precast concrete wall (PCW) may occur problems such as time delay, labour intensive, varies in output of product positioning and safety issues as manual handling methods are involved. Therefore, a new innovation idea called Precast Concrete Installer (PCI) Robot is made as a solution to the problems identified. The objectives of the research are to identify the current issues and problems on the installation process of PCW, to determine various innovation approaches and to propose a new innovation idea on improving the installation process of PCW. In order to achieve the objectives, the method used to conduct the research is desk study on the relevant topics related to the PCI Robot. Therefore, the critical review will become the basis of a new concept for PCI Robot to solve the problems identified. From the review, it was found that the innovative approaches to the PCI Robot may include erection crew, auxiliary tools and machineries. Therefore, the PCI Robot is expected to enhance the safety environment as well as quality for the future construction purpose.